Deficiencies in New Zealand Delegated Legislation - Palmer, Geoffrey (Victoria University of Wellington Law Review, 1999)
In this article, the author, a former Minister of Justice and Prime Minister, examines the history and role of statutory regulations. Processes for reviewing regulations, especially through the Parliamentary Regulations Review Select Committee, have been significant in offering protection against undesirable regulation-making. The courts have played a lesser role in this regard and the author calls for them to be "a little more robust in their approach to delegated legislation". The development of a third tier of law-making, by the use of so-called "rules", is worrying, as these rules receive the same scrutiny as regulations neither before nor after their making. The author recommends that either we abandon making such rules or we introduce processes which are more formal and transparent. At present, "the coherence of our legal system is threatened".